Jamaica (International Monetary Fund, 2022)
Jamaica was hit hard by the pandemic. An early lockdown in the Spring of 2020 helped contain the number of Covid-19 cases but the impact on the economy was severe, with real GDP shrinking by 10 percent. To counter the social and economic effects of the pandemic, the government temporarily reduced the fiscal balance target from +0.7 to -3 percent of GDP, increased spending on health and social protection and reduced the VAT rate. The central bank injected liquidity and encouraged loan moratoria to provide temporary support to the private sector. Growth is expected to rebound to 4.7 percent in 2021 and 4.3 percent in 2022. Downside risks to the outlook are significant, notably from Covid-19
10.5089/9798400203374.002
Keywords: Graue Literatur; inflation expectation; CPI index; tourism stopover visitor; decline in inflation; inflation in December; Global; Caribbean; Europe; Inflation; COVID-19; Fiscal responsibility law; International Agreements and Observance; International Organizations; Monetary Policy; Statistics; Money and Monetary Policy; Diseases: Contagious; Debt; Debt Management; Sovereign Debt; Price Level; Deflation; Health Behavior; National Government Expenditures and Related Policies: General; Data Collection and Data Estimation Methodology; Computer Programs: Other; Monetary economics; International institutions; Public finance & taxation; Macroeconomics; Infectious & contagious diseases; Econometrics & economic statistics; Financial administration & public finance law; International organization; Public debt; International Economics; Health; Expenditure; Public Finance; Monetary policy; International agencies; Debts; Public; Prices; Communicable diseases; Expenditures; Public; Fiscal policy